2020
DOI: 10.1038/s41598-020-71478-w
|View full text |Cite
|
Sign up to set email alerts
|

Four meta-analyses across 164 studies on atypical footedness prevalence and its relation to handedness

Abstract: Human lateral preferences, such as handedness and footedness, have interested researchers for decades due to their pronounced asymmetries at the population level. While there are good estimates on the prevalence of handedness in the population, there is no large-scale estimation on the prevalence of footedness. furthermore, the relationship between footedness and handedness still remains elusive. Here, we conducted meta-analyses with four different classification systems for footedness on 145,135 individuals a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 241 publications
6
25
0
Order By: Relevance
“…Similar to the results obtained by Suzuki et al 34 , the item “foot used to kick a ball”, which is often used as the only assessment item in footedness studies, does not seem to be the optimal choice to investigate heritability of laterality. We previously showed that measuring footedness in terms of kicking results in a similar prevalence of left-footedness 29 compared to inventories such as the Waterloo footedness questionnaire (WFQ) 67 or lateral preference inventory (LPI) 68 . However, as kicking is often only assessed in one trial, the prevalence of mixed-footedness is systematically lower in studies using kicking to assess footedness 29 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similar to the results obtained by Suzuki et al 34 , the item “foot used to kick a ball”, which is often used as the only assessment item in footedness studies, does not seem to be the optimal choice to investigate heritability of laterality. We previously showed that measuring footedness in terms of kicking results in a similar prevalence of left-footedness 29 compared to inventories such as the Waterloo footedness questionnaire (WFQ) 67 or lateral preference inventory (LPI) 68 . However, as kicking is often only assessed in one trial, the prevalence of mixed-footedness is systematically lower in studies using kicking to assess footedness 29 .…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that measuring footedness in terms of kicking results in a similar prevalence of left-footedness 29 compared to inventories such as the Waterloo footedness questionnaire (WFQ) 67 or lateral preference inventory (LPI) 68 . However, as kicking is often only assessed in one trial, the prevalence of mixed-footedness is systematically lower in studies using kicking to assess footedness 29 . Equally the low SNP-h 2 for eye preference in ALSPAC could reflect the poor quality of this phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, it must be noted that motor functions deserve a special place in this list, particularly because of the peculiar status of handedness as a function that is lateralized both behaviorally and neurologically from early childhood (Bondi et al, 2020 ): around 90% of humans show a preference for using the right hand, which is controlled by the left brain hemisphere (McManus, 2002 ; Tommasi, 2009 ). Additionally, footedness should also be granted a special position in the field of human laterality, having been shown to share similarities with handedness both in behavioral and neuropsychological terms, and to be less influenced by cultural and social factors than handedness (Elias and Bryden, 1998 ; Tran et al, 2014 ; Packheiser et al, 2020a , c ). Population-level motor asymmetries which seem to be precursors of handedness are observed already during fetal life (Hepper et al, 1990 ; Hepper, 2013 ; see also Baciadonna et al, 2010 for analogous early predictors of limb laterality in a non-human species), speaking in favor of a substantial genetic contribution.…”
Section: Behavioral Epigenetics and The Development Of Lateralizationmentioning
confidence: 99%